2021
DOI: 10.1080/1828051x.2021.1875337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a multicarbohydrase supplementation to diets varying in metabolisable energy level on the performance, carcase traits, caecal microbiota, intestinal morphology, and nutrient digestibility in broiler chickens

Abstract: This trial was conducted to investigate the effects of multi-carbohydrase supplementation on the performance, carcase traits, intestinal histomorphology, caecal microbiota and nutrient digestibility of broiler chickens fed diets with varying energy levels. A total of 400-day-old male chicks were allocated into eight dietary treatments in a 4 Â 2 factorial arrangement with 5 replicates per treatment. There were 4 dietary energy levels (the standard breed recommendation and reductions of 50, 100 and 150 kcal/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
8
7
0
Order By: Relevance
“…According to the results of the current study, dietary ME content had no effect on the histomorphological characteristics of the duodenal and jejunal mucosa. These findings are consistent with those of previous studies, which reported no significant variation in the gut histomorphological characteristics of broiler chickens when dietary energy was reduced by 100 kcal/kg ( Wickramasuriya et al, 2019 ) or 150 kcal/kg ( Attia et al, 2021 ). However, the current study found that the duodenum and jejunum of broiler chickens fed a low-CP diet showed a significant trend toward a lower VH when compared to the normal-CP group.…”
Section: Discussionsupporting
confidence: 93%
“…According to the results of the current study, dietary ME content had no effect on the histomorphological characteristics of the duodenal and jejunal mucosa. These findings are consistent with those of previous studies, which reported no significant variation in the gut histomorphological characteristics of broiler chickens when dietary energy was reduced by 100 kcal/kg ( Wickramasuriya et al, 2019 ) or 150 kcal/kg ( Attia et al, 2021 ). However, the current study found that the duodenum and jejunum of broiler chickens fed a low-CP diet showed a significant trend toward a lower VH when compared to the normal-CP group.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the DM and GE digestibility of combined soybean meal 1 were significantly decreased compared with other soybean meals. Interestingly, CP digestibility in our study was lower than that in other studies ( Attia et al., 2021 ), but similarly to that obtained by Liu et al. (2021) .…”
Section: Resultssupporting
confidence: 85%
“…In addition, intestinal morphology was improved by carbohydrase supplementation mainly due to reduced viscosity of digesta ( Jang et al., 2020 ). Similarly, Attia et al. (2021) also stated that the supplementation of multi-carbohydrase could additionally or synergistically improve gut microbiota and intestinal histomorphology.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary energy density profoundly influences microbiota composition and abundance ( Adewole and Akinyemi, 2021 ). Low energy density decreased the amount of nutrients available for bacterial fermentation, thereby reshaping bacterial structure ( Attia et al, 2021 ). In addition, nutrient utilization of microbiota in hindgut is closely related to energy metabolism ( Yamamura et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%